Copyright and Related Rights According to Jordan Legislations - Ali Melhem, Ayman Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Study purpose : To identify copyright , materialistic and legal reality , and explain these rights protection and the actual need for legal protection , then identifying positives and negatives for the legislative situation for such kind of rights in Jordan . Also to indicate the defect and shortage if available , in addition providing suggestions and recommendations that may overcome this defect. Conclusion : By the end of this study , hope to be succeeded in referring to the main points of copyright and related protection which was presented through two demands ; literary and financial right , as I identify these rights and the difference between them and each right importance and characteristics .As by the second chapter , I present copyright related rights through two sides , the first is blogging right and other related rights for its identification , and characteristics. The second side is copyright protection whether by judicial control or before civil or penal courts . Through this research ; the researcher had the following recommendations : The researcher hope Jordan legislator to indicate the crimes against copyright with crime kind and it’s danger , as texts indicating copyright protection came common and not classified.